What would happen if?: A comparison of fathers’ and mothers’ questions to children during a science activity - Leech, Kathryn; Chandler-Campbell, Ian L.; Alton, Jenna; Corriveau, Kathleen H. (Frontiers in Psychology, 2023)
Parents’ questions are an effective strategy for fostering the development of young children’s science understanding and discourse. However, this work has not yet distinguished whether the frequency of questions about scientific content differs between mothers and fathers, despite some evidence from other contexts (i.e., book reading) showing that fathers ask more questions than mothers. The current study compared fathers’ and mothers’ questions to their four- to six-year-old children (N = 49) while interacting with scientific stimuli at a museum research exhibit. Results indicated that fathers asked significantly more questions than mothers, and fathers’ questions were more strongly related to children’s scientific discourse. Results are discussed in terms of the importance of adult questions for the development of children’s scientific understanding as well as broadening research to include interlocutors other than mothers.